Post biopsy evaluation of mucoepidermoid carcinoma excision on maxillary using CBCT: a case report - Fauziyah, Erlina; Pamungkas, Aries Sugih Budhiana; Cahyareni, Firlana; Hanafi, Eva Yulianti; Gustianto, Yudhy; Pramanik, Farina; Putri, Annisa (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: The purpose of this case study is to report the postoperative evaluation of a case of Mucoepidermoid Carcinoma occurring in the maxilla using CBCT. Case Report: A 44-year-old woman came to the Dental Radiology Installation of the Padjadjaran University Dental and Oral Hospital with complaints of swelling in the right maxillary region since 1 year ago accompanied by pain and could not open her mouth. The patient brought a referral letter for CBCT photos with a clinical diagnosis of Maxillary Tumour Dextra Post Biopsy Excision in the Maxillary Dextra region with HPA Mucoepidermoid Carcinoma a.r Maxillary Dextra. CBCT results showed tooth loss in areas 16, 17, and 18 accompanied by trabeculae loss at the posterior alveolar process support and partial bone thinning at the maxillary tuberosity. The loss of some hard tissue was likely part of the tissue taken for biopsy. The average density in these areas was ± 49 HU. Conclusion: Lesions can be analysed using qualitative and quantitative methods with 3D CBCT.